2008
DOI: 10.1007/s12185-008-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac toxicity of high-dose cyclophosphamide and melphalan in patients with multiple myeloma treated with tandem autologous hematopoietic stem cell transplantation

Abstract: Tandem autologous hematopoetic stem cell transplantation (HSCT) is an effective treatment in patients with multiple myeloma (MM). Patients receive high-dose cyclophosphamide (CY) followed by two myeloablative dosages of melphalan (MEL). Cardiotoxicity treatment related data are scanty. In 30 patients with MM chemotherapy was followed by high-dose CY (cycle CY), and two autologous tandem HSCT treatments with MEL (cycles MEL I and MEL II). During each 15-day treatment troponin I (TnI), brain natriuretic peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
2
25
0
2
Order By: Relevance
“…Other recent reports are consistent with these findings, showing a close relationship between NP and the development of subclinical myocardial injury due to the administration of chemotherapy [51,73,76,[81][82][83][84]. Only a few studies [53,58,75] in patients receiving AC-based CT found no correlation between NT-proBNP increase and development of cardiac dysfunction.…”
Section: Natriuretic Peptidessupporting
confidence: 68%
“…Other recent reports are consistent with these findings, showing a close relationship between NP and the development of subclinical myocardial injury due to the administration of chemotherapy [51,73,76,[81][82][83][84]. Only a few studies [53,58,75] in patients receiving AC-based CT found no correlation between NT-proBNP increase and development of cardiac dysfunction.…”
Section: Natriuretic Peptidessupporting
confidence: 68%
“…In patients in whom the level of NT-proBNP increased and remained elevated after 72 h (group C, 32% of patients), we observed a deterioration of diastolic indexes (mitral deceleration time, isovolumetric relaxation time, and mitral E/A ratio) and a decrease in LVEF (from 62.8% to 45.6; p<0.001), with a strong relationship between the NTproBNP value at 72 h and LVEF changes at 12 months versus baseline (r=0.78; p<0.001). Our findings are consistent with more recent reports in which a close relationship between NP and the development of subclinical myocardial injury due to the administration of chemotherapy was found [49,50].…”
Section: Schlüsselwörtersupporting
confidence: 94%
“…Протокол ЭхоКГ у онкологических больных не отличается от такового при обследовании больных с ССЗ. При использовании высо-кодозной ХТ и аутологичной ТКМ особое внимание уде-ляется показателям систолической и диастолической функции ЛЖ [61,62] -фракции выброса (ФВ), скорости раннего и позднего наполнения ЛЖ и их соотношения [62,63]. ФВ менее 40-45% может быть противопоказани-ем к проведению специфической терапии ОЗ [58].…”
Section: ие чазова и соавтunclassified
“…Тщательный сбор анамнеза и изу-чение медицинской документации, имеющейся у больно-го, может помочь выявить ССЗ и факторы, предраспола-гающие к развитию кардиотоксичности. Всем больным ОЗ до начала противоопухолевого лечения необходимо оценить состояние ССС, включая клинический статус, проведение электрокардиографии, суточного монитори-рования электрокардиограммы по Холтеру для выявления нарушений ритма и/или проводимости сердца [56][57][58][59][60][61][62][63][64][65][66]. ЭхоКГ должна проводиться у больных, которым планиру-ется лечение антрациклинами, трастузумабом, ингибито-…”
Section: ие чазова и соавтunclassified